LAW AND/OR ACCOUNTING. - Gibson, Joseph E. (The Accounting Review, 1962)
The interdependence of law and accounting, too well established to be denied, is inbred in the professions. Law plays a vital role in the training of the accounting student; in fact, much of accounting is law. The course commonly called "Business Law" is but one concentrated exposure to problems in law which accounting students encounter in various forms in other courses. On the other hand, the commercial courses in law school-partnerships, corporations, bankruptcy, and taxation, to name a few-lose a great deal of their meaning unless the law student has a good understanding of the financial, or accounting, basis underlying the transactions. The accounting curriculum certainly does not purport to train the accounting student for the general practice of law, but, of necessity, the accounting student must be extensively exposed to many areas of the law or he will not be qualified to fulfill his purpose as an analyst, examiner of accounts, or as an interpreter of financial statements. Without question, some accounting students acquire, and in some areas retain, more legal knowledge, than do some legal practitioners, but the legal knowledge of an accountant is admittedly incidental to his principal purpose.